REDD+ as Result‐based Aid: General Lessons and Bilateral Agreements of Norway. Issue 2 (19th June 2016) - Angelsen, Arild
Abstract: The initiative known as Reducing Emissions from Deforestation and Forest Degradation (REDD+) officially became part of the international climate agenda in 2007. At that time, REDD+ was an idea regarding payment to countries (and possibly also projects) for reducing emission from forests, with funding primarily from carbon markets. The initiative has since become multi‐objective in nature; the policy focus has changed from a payments for environmental services (PES) approach to broader policies, and international funding primarily originates from development aid budgets. This "aidification" of REDD+ has made the program similar to previous efforts using conditional or results‐based aid (RBA). However, the experience of RBA in other sectors has scarcely been addressed in the REDD+ debate. The alleged advantages of RBA are poorly backed by empirical research. This paper reviews the primary challenges in designing and implementing a system of RBA, namely, donor spending pressure, performance criteria, reference levels, risk sharing, and funding credibility. It then reviews the four partially performance‐based, bilateral REDD+ agreements that Norway has entered with Tanzania, Brazil, Guyana, and Indonesia. These agreements and the aid experience provide valuable lessons for the design and implementation of future REDD+ mechanisms.